2011
DOI: 10.1111/j.1365-2648.2010.05582.x
|View full text |Cite
|
Sign up to set email alerts
|

Online communities of practice as a communication resource for community health nurses working with homeless persons

Abstract: Online communities of practice can be valuable to nurses in specialized fields with limited peer support and access to information resources. Tacit knowledge development is important to nurses working with homeless populations: this needs to be valued in conjunction with scientifically based knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 48 publications
1
44
0
Order By: Relevance
“…Communication options in most studies included an asynchronous method, either by email or discussion boards [23,24,26,28,34,37,39,42], while some studies used these with a mix of features including chat, content sharing and synchronous web-meetings [23,34,35,39]. Email reminders were also suggested to be useful [26,37,41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication options in most studies included an asynchronous method, either by email or discussion boards [23,24,26,28,34,37,39,42], while some studies used these with a mix of features including chat, content sharing and synchronous web-meetings [23,34,35,39]. Email reminders were also suggested to be useful [26,37,41].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies used passwords [28,42] though lost passwords and online delivery created barriers for others [37,39,40]. The online environment was of real benefit to most [24,27,35], though one study found that the culture of face-to-face interaction amongst nurses was a barrier to use of online environments [30].…”
Section: Resultsmentioning
confidence: 99%
“…The increased connectedness that results from information and communication technologies (ICT) has overcome geographic barriers of rural or widely dispersed health practitioners, with variable access to peers, specialists, and information resources in other disciplines [6-8]. These tools can facilitate the evolution of virtual “communities of practice” (VCoP) [9], groups of individuals who share interests and expertise through online collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…This was done to understand key elements about the role that online CoPs had played in other related health contexts. Studies in community health nursing [10],m e n t a lh e a l t h research [32], orthopaedic surgery [33],i d e n t i fied that online CoPs help to promote dialogue and networking among health professionals online without needing face-to face commitments. Therefore participating in online discussion saved time and strengthened peer support that would otherwise be unavailable to practitioners who worked in isolated circumstances.…”
Section: Stage 1: Developing a Middle Range Theorymentioning
confidence: 99%
“…In the health context, CoPs that allow health practitioners share best practices virtually have become an important mechanism for supporting practice among those who may be geographically dispersed in nursing, community health nursing, psychiatry, among others [8][9][10][11][12].A d v a n c e si ni n t e r n e t and intranet based applications have facilitated the conversion of tacit-explicit knowledge by allowing practitioners to express their own everyday experiences, key issues, ideas and reflections of practice through online forums, blogs and discussion forums [13]. Members participate in these online CoPs by reading or posting, sharing and adapting, applying and improving, reflecting and sharing their reflection, collaborating and assisting others [14].…”
Section: Introductionmentioning
confidence: 99%